Webometric analysis of the availability of semaglutide-based anti-obesity drugs - Kremin, Yuliia; Dorykevych, Kateryna; Shunkina, Sofiia (Annals of Mechnikov’s Institute, 2024)
Introduction. According to the WHO, in 2022 every eighth person in the world suffers from obesity. Future forecasts are that by 2025, 167 million adults and children will experience poor health as a result of being overweight or obese. Accordingly, this issue gives rise to the need for people to find weight loss methods, and in recent years, drugs based on semaglutide have become in great demand as an easy way to lose weight, despite the presence of a large number of possible side effects. The purpose of this work was a webometric analysis of the availability of such drugs on the market of Ukraine. Materials and methods. The research materials were data from online search pages for medicines in pharmacies of Ukraine, as well as 12 websites that illegally offer to purchase the above-mentioned drugs were investigated. Webometrics, modeling and scientific generalization were used among the methods. Research results. After analyzing the pharmaceutical market of Ukraine, we found out that there is only one semaglutide-based drug registered in Ukraine – Ozempik. Currently, there is a shortage of this medicine, as there were only 27 offers for the availability of this drug in Ukrainian pharmacies as of 07/23/2024. Nevertheless, illegal Internet platforms (we have identified 10 online services that position themselves as platforms for the sale of drugs by delivery / imports them from European pharmacies, and 2 online services with biologically active supplements and sports nutrition) offer easy availability of Ozempik (injectable dosage form). In addition, there are two other medicines available for purchase on online resources - Vegovi (injectable dosage form) and Ribelsus (tablet dosage form), which are not registered in our country. Conclusion. The availability of semaglutide-based drugs in Ukraine was studied using a webometric search. Its shortage in licensed distribution points (pharmacies) was established, while the unimpeded presence of unlicensed sales was revealed, which requires strengthening of state control over the illegal trade in these medicines.